Acoustics and the well-being of children and personnel in early childhood education and care - Martikainen, Silja; Prawda, Karolina; Ståhlberg-Aalto, Freja; Lautanala, Ida; Kostilainen, Kaisamari; Välimäki, Vesa; Tervaniemi, Mari (Frontiers in Education, 2023)
Studies implementing a multimethod perspective in evaluating the acoustics of early childhood education and care (ECEC) spaces both quantitatively and qualitatively are still scarce. In this study the acoustic environments (noise levels and reverberation times) of seven Finnish ECEC group's premises were examined in association with personnel's (N = 22) and children's (N = 71) well-being. The findings were further elaborated by documentation of the ECEC spaces and semi-structured interviews with the ECEC personnel detailing their views on the acoustic environment of the daycare buildings and how and if the acoustics should be improved. The results showed that noise exceeding 70 dB affected personnel's vocal health negatively, whereas no associations were found regarding acoustics and children's or personnel's well-being. Based on the interviews, sound spreading, poor insulation, and hard surfaces add to negative experiences of noisiness. ECEC groups need spaces that can be closed and acoustically separated from each other and from other groups. The possibility to close a space supports the perceived well-being of the users and provides a more varied and individualized use of the spaces.